222 Analysis the characters of clinical pathology of locally advanced cervical cancer after neoadjuvant chemotherapy. (18th September 2019) - Zhao, Q; Hui, Z
Abstract : Objectives: To analyze the charaters of clinical pathology of locally advanced cervical cancer after arterial interventional neoadjuvant chemotherapy, and to provide evidence for the curative efficacy of neoadjuvant chemotherapy for locally advanced cervical cancer. Methods: 132 cases of IB2 or IIA2 stage cervical cancer patients' materials were r etrospectively collected. 62 cases were in study group (who received paclitaxel carboplatin regimen of neoadjuvant chemotherapy before operation), and 70 cases were in control group (who received operation directly). The clinical charactors and postoperative pathologies were analyzed. Results: Between two groups. there were no significant differences in patients' ages, FIGO stages, histology, and cell differentiations. As for the postoperative pathology, the rate of mascular invasive ≥1/2 was 50% in study group, and 75.0% in control group. The difference was significant (p=0.038002). The vascular invasive rate was 11.1% in study group, and 68.6% in control group. The difference was significant (p=0.001). The lymphatic invasive rate was 5.6% in study group, and 18.8% in control group. The difference was significant (p=0.0126). The rate of Ki67 ≥70% was 27.8% in study group, and 68.8% in control group. The difference was significant (p=0.002). Conclusions: The curative efficiency of neoadjuvant chemotherapy for locally advanced cervical cancer is extremely good for short stage and local lesions. Neoadjuvant chemotherapy could significant decrease vascular invasive rate, lymphatic invasive rate and Ki67 positive rate. The long term curative efficiency of neoadjuvant chemotherapy for locally advanced cervical cancer is still need further study.